“Evaluación de tres dosis de ácidos humicos y fulvicos con macro y micro elementos, en el cultivo de lechuga (lactuca sativa L.) variedad grand rapids waldemanS strain, bajo condicones agroecológicas en la provincia de Lamas - Ríos Trigozo, María Del Pilar (2015)
This paper titled Evaluation of three doses of humic and fulvic acids with macro and micro elements in growing lettuce (Lactuca sativa l.) Grand Rapids Waldeman··s variety Strain, under agroecological conditions in the Province of Lamas, had objective: To determine the dose increased efficiency of humic and fulvic with macro and micro elements in crop yield Lettuce (Lactuca sativa L.). Which was held at the plantation "El Pacifico" owned lng. Jorge Luis Pelaez Rivera, located in the district of Lamas, Lamas province, San Martín department. Statistical design of randomized complete block (RCBD) with four blocks, four treatments and a total of 16 experimental units were used. Statistical analysis was performed with SPSS 19 confidence levels 5% and 1 %. A control treatment (TO) was used and three treatments with 20, 40 and 60 l.ha-1 humic acid, fulvic with macro and micro elements (Humifarm Plus) and conclusions drawn were: Treatment T3 (60 l.ha- 1 ) the highest mean performance with 67,362.5 kg ha-1 and plant weight, plant height, number of leaves per plant with 134. 73 grams, 23.0 cm, 5.1 leaves respectively was obtained. The percentage of seizure of seedlings in final field and the diameter of the stem have not become variables that explain the effects of the treatments. The growing applications of humic and fulvic acids described positiva linear responses on plant height, plant weight, number of leaves per plant and yield in kg ha-1 . Keywords: microelements, macroelements, humic and fulvic acids